Phylogenomics of montane frogs of the Brazilian Atlantic Forest is consistent with isolation in sky islands followed by climatic stability - Pie, Marcio R. (2018)
Despite encompassing a relatively small geographical area, montane regions harbour disproportionately high levels of species diversity and endemism. Nonetheless, relatively little is known about the evolutionary mechanisms that ultimately lead to montane diversity. In this study, we used target capture of ultraconserved elements to investigate the phylogenetic relationships and diversification patterns of Melanophryniscus (Bufonidae) and Brachycephalus (Brachycephalidae), two frog genera that occur in sky islands of the southern Atlantic Forest of Brazil. Specifically, we tested whether diversification of montane species in these genera could be explained by a single climatic shift leading to isolation in sky islands, followed by climatic stability that maintained populations in allopatry. In both genera, the topologies inferred using concatenation and coalescent-based methods were concordant and had strong nodal support, except for a few recent splits, which nevertheless tended to be supported by more informative loci. Estimation of divergence time of a combined dataset using both genera is consistent with a concordant timing of their diversification. These results support the scenario of diversification by isolation in sky islands and suggest that allopatry attributable to climatic gradients in montane regions is an important mechanism for generating species diversity and endemism in these regions.